Differences and similarities between first and second languages: A functional and pedagogical analysis - Zulkifley Hamid; Rahim Aman (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2006)
This article examines the differences and similarities between first and second languages. The discussion focuses on the aspects of function and pedagogy. With respect to differences, attention is given to aspects related to language as a choice, the method of knowledge acquisition for first and second languages, and the different functions of first and second languages. For similarities, the discussion focuses on the importance of acquiring both first and second languages holistically. Although there are many differences between first and second languages, there are also similarities